Enhancing Growth in Vigna radiata through the Inhibition of Charcoal Rot Disease: A Strategic Approach Using Plant Growth-Promoting Rhizobacteria - Imran Khan; Sahar Ghulam Mohyuddin; Sohail; Shah Zaman; Muhammad Qadir; Juxian Guo; Guihua Li (Microorganisms)
Macrophomina phaseolina is a vital seed and soil-borne phytopathogen responsible for substantial crop yield losses. Although various methods exist for managing soil-borne pathogens, such as agronomic practices, chemical treatments, and varietal tolerance, biological control utilizing plant growth-promoting rhizobacteria (PGPR) or their secondary metabolites presents promising avenues. In this study, a screening of 150 isolates from the rhizosphere of Vigna radiata L. was conducted to identify strains capable of promoting host growth and controlling charcoal rot disease. Among the tested isolates, only 15 strains demonstrated the ability to produce plant growth-related metabolites, including indole acetic acid, hydrogen cyanide, ammonia, and lytic enzymes, and solubilize inorganic phosphate. Subsequently, these potent strains were evaluated for their antifungal activity against Macrophomina phaseolina in vitro. Three strains, namely MRP-7 (58% growth inhibition), MRP-12 (55% growth inhibition), and MRP-8 (44% growth inhibition), exhibited the highest percent growth inhibition (PGI.). Furthermore, a pot experiment demonstrated that the selected strains acted as effective growth promoters and ROS (reactive oxygen species) scavengers, and served as potential biocontrol agents, significantly reducing the incidence of charcoal rot disease and improving various agronomic attributes of the host plant. These findings highlight the potential of these strains to be utilized as biofertilizers and biocontrol agents for sustainable agricultural practices.